1999
DOI: 10.3109/13651509909024771
|View full text |Cite
|
Sign up to set email alerts
|

Long term efficacy of paroxetine in major depression: A study with plasma levels

Abstract: Depressive disorders can be regarded as recurrent and chronic conditions that may reduce the quality of life and work output of patients. Data on the long-term efficacy of paroxetine appear to indicate that it is an effective maintenance treatment. Our aim was to measure paroxetine concentrations in plasma in order to optimize its clinical efficacy and tolerability during long-term treatment. We studied 35 patients aged 23-70 years, suffering from Major Depressive Disorder (recurrent). These patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In conclusion this study, assessed in a naturalistic, observational setting, confirm the good efficacy and tolerability of SRT at low dosages in the long-term treatment of major depression. According to our data, drug plasma level monitoring of SRT, like other SSRIs (Mauri et al, 1999;Lundmark et al, 2000), could be useful in optimizing the response in non-or partialresponders, but this requires a separate examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion this study, assessed in a naturalistic, observational setting, confirm the good efficacy and tolerability of SRT at low dosages in the long-term treatment of major depression. According to our data, drug plasma level monitoring of SRT, like other SSRIs (Mauri et al, 1999;Lundmark et al, 2000), could be useful in optimizing the response in non-or partialresponders, but this requires a separate examination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies suggest that the risk of depression increases with each past episode, subsequent episodes often occur sooner, they are of longer duration, more severe, less responsive to treatment and they carry renewed risks of psychosocial impairment and suicide (Keller, 1999;Mauri et al, 1999;Zajecka, 2000). Therefore, a 3-6 months' continuation therapy after acute stabilization should be considered for all depressed patients and maintenance therapy should be considered for many of them (Hirschfeld, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Taking these findings into account, it is plausible that the plasma paroxetine levels play a role in deciding the time to treatment response, but that the levels are independent of the final response to the paroxetine treatment. In contrast, Mauri et al (1999) reported that a therapeutic window of paroxetine is 70 ng/ml. Lundmark et al (2000) have also demonstrated that a serum paroxetine concentration of 25-50 ng/ml appears to be adequate for efficacy based on therapeutic drug monitoring.…”
Section: Discussionmentioning
confidence: 95%
“…Gilles et al (2005) reported that the ideal paroxetine concentration at 2 weeks was 43 ng/ml, with poor outcomes being observed at either higher or lower concentrations. Mauri et al (1999) paroxetine levels in treatment for chronic symptoms should be between 20 and 70 ng/ml. These results suggest that a therapeutic window might exist in paroxetine treatment in depressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma level determination can be an useful tool to allow adjusting the dose in each individual patient [52].…”
Section: Paroxetinementioning
confidence: 99%